The Process-Outcome Disparity in Culturally Responsive Physics Instruction: A Qualitative Case Study from Indonesia - Nurul Husnah; M. A. Martawijaya; Mahir Mahir (Journal of Social Work and Science Education, 2026)
This study examines the implementation and contextual relevance of the CRT approach in Indonesian senior high school Physics education. Employing a qualitative case study design, data were gathered through classroom observations and systematic document analyses (RPP and student outputs) from a single subject at State Senior High School 10 Makassar. The key results demonstrate that while the teacher achieved high pedagogical fidelity successfully fostering inclusive interactions (Score 5.0) and stimulating critical thinking (Score 4.0) by contextualizing abstract concepts the implementation was structurally incomplete. This resulted in an extreme cultural competence gap, characterized by high teacher effort (Score 4.5) contrasting dramatically with minimal cultural manifestation in student outputs (Score 1.0). This disparity is primarily attributed to a structural weakness in formal assessment design that fails to explicitly demand culturally reflective outcomes, coupled with significant external systemic barriers (50% minimal community participation). The research’s novelty lies in its triangulated, quantitative-qualitative documentation analysis used to precisely measure this 4.5 vs. 1.0 disparity, shifting the scholarly focus from individual capacity to systemic issues. The findings offer crucial practical implications for urgent assessment reform to mandate culturally reflective learning outcomes and emphasize the contribution of strengthening holistic institutional commitment and community partnership to bridge the process-to-outcome gap.